Potential for residual load balancing of a frozen food manufacturing plant – A heuristic approach. (August 2018) - Naegler, Tobias; Simon, Sonja
Graphical abstract: Model structure of the frozen food manufacturing plant. Thermal energy storages (TES) decouple useful energy demand (e.g. process heat, process cold) from useful energy generation. They thus allow flexible net power consumption. HT-TES: high temperature thermal energy storage; LT-TES: low temperature thermal energy storage, C-TES: cold thermal energy storage; CHP: combined heat and power production, IIC: illumination, information, communication. Peak loads on the right hand side refer to useful energy demand. Abstract: We simulated the potential of a frozen food manufacturing plant to contribute to the balancing of the residual load under the premise that the plant's production processes remain unaffected. The plant's technical balancing options comprise both demand side management (chillers for process cold, electric process heat generation) and dispatchable power generation (by a combined heat and power (CHP) plant). In the model, the decoupling of useful energy demand (heat and cold) from power consumption and power generation was enabled by the use of a high temperature thermal energy storage (HT-TES), a cold thermal energy storage (C-TES), and flexible cold storage warehouse temperatures. The analysis shows that the balancing potential basically depends on two factors: (1) plant operation (reflected by gross power demand and power generation) in the inflexible reference case, which defines to which extend power demand and generation can be increased or reduced when the plant is operated flexibly, and (2) the capacity of the thermal energy storages (TES) relative to the typical length of deficit and surplus periods. The model further shows that a heuristic algorithm controlling the operation of the plant's flexible units can exploit a large fraction of the technical balancing potential of the plant.